2008
DOI: 10.1007/s10827-008-0103-9
|View full text |Cite
|
Sign up to set email alerts
|

Calcium sensitive non-selective cation current promotes seizure-like discharges and spreading depression in a model neuron

Abstract: As described by others, an extracellular calciumsensitive non-selective cation channel ([Ca 2+ ] o -sensitive NSCC) of central neurons opens when extracellular calcium level decreases. An other non-selective current is activated by rising intracellular calcium ([Ca 2+ ] i ). The [Ca 2+ ] osensitive NSCC is not dependent on voltage and while it is permeable by monovalent cations, it is blocked by divalent cations. We tested the hypothesis that activation of this channel can promote seizures and spreading dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…An exception was area CA1 in rat and mouse hippocampus, where the packing density of neurons is higher, promoting ephaptic interactions that are thought to be enhanced by lowered extracellular calcium. On the other hand, cation channels [ 37 ] and more recently certain TRP channels are activated by decreasing either Ca or Mg concentration [ 91 ]; this is not only important for spreading depolarization [ 80 ] but possibly also for generation of seizures and cell death [ 62 ]. The regulation of these excitatory channels by Ca and the activitydependent decrease in extracellular Ca suggests a new mechanism for seizure spread and for modifying seizure generalization.…”
Section: Channelopathiesmentioning
confidence: 99%
“…An exception was area CA1 in rat and mouse hippocampus, where the packing density of neurons is higher, promoting ephaptic interactions that are thought to be enhanced by lowered extracellular calcium. On the other hand, cation channels [ 37 ] and more recently certain TRP channels are activated by decreasing either Ca or Mg concentration [ 91 ]; this is not only important for spreading depolarization [ 80 ] but possibly also for generation of seizures and cell death [ 62 ]. The regulation of these excitatory channels by Ca and the activitydependent decrease in extracellular Ca suggests a new mechanism for seizure spread and for modifying seizure generalization.…”
Section: Channelopathiesmentioning
confidence: 99%
“…Besides K + , changes in the distribution of Ca 2+ also influenced the neuron responses and these effects are also presented. In a companion paper we explore the potential role of calcium-sensing non-specific cation current in facilitating seizures and SD (Somjen et al 2008).…”
mentioning
confidence: 99%
“…These results suggest that anti-TRPC3 antibody and Pyr3 completely block TRPC3 channels and that low Ca/low Mg-induced depolarization in dysplastic cortex is primarily mediated by TRPC3 channels. The small, residual depolarization after TRPC3 channels are blocked may be mediated by other channels such as other nonselective cation ion channels or L-type Ca 2ϩ channels (Pohl et al 1992;Somjen et al 2009). …”
Section: Blocking Trpc3 Greatly Reduced Low Ca/low Mg-induced Depolarmentioning
confidence: 99%
“…Other studies have demonstrated that low Ca can excite hippocampal pyramidal neurons through activation of novel and unidentified nonselective cation channels that are not blocked by specific inhibitors of known voltage-gated or ligand-gated ion channels (Chu et al 2003;Xiong et al 1997;Xiong and MacDonald 1999). A computer modeling study showed that activation of nonselective cation channels in low Ca is sufficient to generate epileptiform activity (Somjen et al 2009). Another study in cultured pyramidal neurons revealed that activation of those channels could induce depolarization in low Ca and low Mg, suggesting that those channels could constitute a major component of enhanced neuronal excitability during epileptic seizures (Xiong et al 2001).…”
Section: Mechanisms Of Hyperexcitability In Low-ca and Low-mg Conditionsmentioning
confidence: 99%
See 1 more Smart Citation